2019
DOI: 10.1097/md.0000000000013960
|View full text |Cite
|
Sign up to set email alerts
|

Serum angiopoietin-2 concentrations of post-PCI are correlated with the parameters of renal function in patients with coronary artery disease

Abstract: Patients with coronary artery disease (CAD) frequently have comorbidity of chronic kidney disease (CKD). Their renal function may deteriorate because of the use of contrast agent after percutaneous coronary intervention (PCI). Angiopoietin-2 (Ang-2), which is highly expressed in the site of angiogenesis, plays an important role in both CAD and CKD. This study aimed to investigate the relation of serum Ang-2 concentrations with the renal function after PCI.This study enrolled 57 patients with CAD undergoing PCI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 46 publications
1
0
0
Order By: Relevance
“…Our present study demonstrated ANGPT2 may potentially serve as a biomarker for diagnosing AAD because ANGPT2 was shown to be independently associated with AAD in our study, indicating its potential diagnostic value for AAD. However, we found ANGPT2 correlated with the creatinine level, consistent with previous findings ( 37 ), suggesting that when using this marker, other confounding factors should be considered. Secondly, up to now the precise mechanisms of AAD remain to be clarified and our present study indicated ANGPT2 may involve in the pathopoiesis of AAD.…”
Section: Discussionsupporting
confidence: 92%
“…Our present study demonstrated ANGPT2 may potentially serve as a biomarker for diagnosing AAD because ANGPT2 was shown to be independently associated with AAD in our study, indicating its potential diagnostic value for AAD. However, we found ANGPT2 correlated with the creatinine level, consistent with previous findings ( 37 ), suggesting that when using this marker, other confounding factors should be considered. Secondly, up to now the precise mechanisms of AAD remain to be clarified and our present study indicated ANGPT2 may involve in the pathopoiesis of AAD.…”
Section: Discussionsupporting
confidence: 92%